Long‐term follow‐up of Chagas heart disease patients receiving an implantable cardioverter‐defibrillator for secondary prevention. Issue 6 (23rd April 2018) - Pavão, Maria Licia Ribeiro Cury; Arfelli, Elerson; Scorzoni‐Filho, Adilson; Rassi, Anis; Pazin‐Filho, Antônio; Pavão, Rafael Brolio; Marin‐Neto, J. Antonio; Schmidt, André
Abstract: Background: Chagas heart disease (CHD) is a dilated cardiomyopathy characterized by malignant ventricular arrhythmias and increased risk of sudden cardiac death (SCD). Much controversy exists concerning the efficacy of implantable cardioverter‐defibrillator (ICDs) in CHD because of mixed results observed. We report our long‐term experience with ICDs for secondary prevention in CHD, with the specific aim of assessing the results in groups with preserved or depressed global left ventricular function. Methods: 111 patients (75 males; 60 ± 12 years) were followed for 1, 948 ± 1, 275 days after ICD. Time to death was the primary outcome; LVEF ≤ 45% the exposure; and age, gender, and ICD therapy delivery the potential confounders. We used time‐to‐event methods and Cox proportional models for analysis, censoring observations at time of death or at 5‐year follow‐up in survivors. Results: Seventy‐two percent of the patients presented at least one sustained ventricular arrhythmia requiring appropriate therapy, and only three patients received inappropriate therapy. Death occurred in 50 (45%) patients, with an annual mortality rate of 8.4%, mostly due to refractory heart failure or noncardiac causes. Unadjusted survival rates were significantly distinct between patients with left ventricular ejection fraction (LVEF) ≤ 45% (26 deaths), 50.5% (95% confidence interval [CI]: 36.2%–63.2%) when compared to patients with LVEF > 45% (10 deaths), 77.6% (95% CI: 62.3%–87.3%, P < 0.01). After adjusting for confounders, low LVEF (hazard ratio [HR]: 5.2, 95% CI: 2.3–11.6), age (HR: 1.04, 95% CI: 1.01–1.07), and female gender (HR: 3.97, 95% CI: 1.85–8.54) were independently associated with the outcome. Conclusions: ICDs successfully aborted life‐threatening arrhythmias in CHD patients. Impaired left ventricular function predicted higher mortality in CHD patients with an ICD for secondary prevention of SCD.